ANALYTHING THE USE OF COLLOQUIALISM IN FICTION - Ma'ripov Jalolkhon.; Salomova O‘g‘iloy (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This section introduces the concept of colloquialism and its importance in fiction. It emphasizes how informal language enhances realism, cultural depth, and emotional relatability. The introduction sets the stage for understanding colloquialism as a dynamic tool in literary narratives. The article highlights how colloquial expressions reveal a character’s background, personality, and socio economic status. Examples from literature, such as Huck Finn, showcase how these informal elements contribute to character distinctiveness.